Transferrin-Conjugated Erianin-Loaded Liposomes Suppress the Growth of Liver Cancer by Modulating Oxidative Stress - Yang, Anhui; Sun, Zhen; Liu, Rui; Liu, Xin; Zhang, Yue; Zhou, Yulin; Qiu, Ye; Zhang, Xinrui (Frontiers in Oncology, 2021)
Background: Liver cancer is one of the most malignant human cancers, with few treatments and a poor prognosis. Erianin (ERN) is a natural compound with multiple pharmacological activities that has been reported to have numerous excellent effects against liver cancer in experimental systems. However, its application in vivo has been limited due to its poor aqueous solubility and numerous off-target effects. This study aimed to improve the therapeutic efficacy of ERN by developing novel ERN-loaded tumor-targeting nanoparticles Results: In this study, ERN was loaded into liposomes by ethanol injection (LP-ERN), and the resulting LP-ERN nanoparticles were treated with transferrin to form Tf-LP-ERN to improve the solubility and enhance the tumor-targeting of ERN. LP-ERN and Tf-LP-ERN nanoparticles had smooth surfaces and a uniform particle size, with particle diameters of 62.60 nm and 88.63 nm, respectively. In HepG2 and SMMC-7721 cells, Tf-LP-ERN induced apoptosis, decreased mitochondrial membrane potentials and increased ERN uptake more effectively than free ERN and LP-ERN. In xenotransplanted mice, Tf-LP-ERN inhibited tumor growth, but had a minimal effect on body weight and organ morphology. In addition, Tf-LP-ERN nanoparticles targeted tumors more effectively than free ERN and LP-ERN nanoparticles, and in tumor tissues Tf-LP-ERN nanoparticles promoted the cleavage PARP-1, caspase-3 and caspase-9, increased the expression levels of Bax, Bad, PUMA, and reduced the expression level of Bcl-2. Moreover, in the spleen of heterotopic tumor model BALB/c mice, ERN, LP-ERN and Tf-LP-ERN nanoparticles increased the expression levels of Nrf2, HO-1, SOD-1 and SOD-2, but reduced the expression levels of P-IKKα+β and P-NF-κB, with Tf-LP-ERN nanoparticles being most effective in this regard. Tf-LP-ERN nanoparticles also regulated the expression levels of TNF-α, IL-10 and CCL11 in serum. Conclusion: Tf-LP-ERN nanoparticles exhibited excellent anti-liver cancer activity in vivo and in vitro by inducing cellular apoptosis, exhibiting immunoregulatory actions, and targeting tumor tissues, and did so more effectively than free ERN and LP-ERN nanoparticles. These results suggest that the clinical utility of a Tf-conjugated LP ERN-delivery system for the treatment of liver cancer warrants exploration.